Public and private sector take Climate-Smart Village scaling to next level in India and Nepal - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
State governments in India and Nepal and private sector corporates in India are increasingly scaling Climate-Smart Villages (CSVs) for building climate-resilient agriculture. The scaling activities build on existing CSVs, and the new initiatives are focusing on increased investments and expansion to new villages.